Customer Relationship Management Information System Analysis Using RFM Dashboard For Customer Segmentation Strategy : Study On A Ritel Fashion Company in Bandung - Sudrajat, Jajat; Maulana, Aris Ilham; Riswaya, Asep Ririh; Marjito, Marjito; Rizqiati, Fitri (LPPM STMIK Mardira Indonesia, 2025)
The progression of information technology compels organizations to adeptly leverage customer data, particularly in mitigating the elevated rate of client attrition resulting from insufficient comprehension of consumer behavior and limited personalization in marketing approaches. This study aims to develop and implement a Customer Relationship Management (CRM) system, coupled with an RFM (Recency, Frequency, Monetary) dashboard, for the fashion enterprise Whoop Culture. This system employs the equal-width intervals binning approach to categorize clients based on purchase frequency, transaction value, and the recency of their latest transaction, thereby facilitating the company's understanding of the needs and preferences of each customer category. This online solution is designed to analyze client data and execute segmentation, facilitating more targeted marketing techniques. This research aims to enhance the company's performance by gaining a deeper understanding of consumer behavior, enabling Whoop Culture to improve customer retention, sales, and resource allocation.